Genetic Diversity and Population Structure of Metaphire vulgaris Based on the Mitochondrial COI Gene and Microsatellites - Fang, Yu; Chen, Jie; Ruan, Honghua; Xu, Nan; Que, Ziting; Liu, Hongyi (Frontiers in Genetics, 2021)
The earthworm species Metaphire vulgaris (a member of the Clitellata class) is widely distributed across China, and has important ecological functions and medicinal value. However, investigations into its genetic diversity and differentiation are scarce. Consequently, we evaluated the genetic diversity of five populations of M. vulgaris (GM, HD, NYYZ, QDDY, and QDY) in Yancheng, China via the mitochondrial COI gene and the novel microsatellites developed there. A total of nine haplotypes were obtained by sequencing the mitochondrial COI gene, among which NYYZ and QDDY populations had the greatest number of haplotypes (nh=5). Further, the nucleotide diversity ranged from 0.00437 to 0.1243. The neighbor-joining trees and the TCS network of haplotypes indicated that earthworm populations within close geographical range were not genetically isolated at these small scale distances. Results of the identification of microsatellite molecular markers revealed that the allele number in 12 microsatellite loci ranged from four to 13. The observed heterozygosity ranged from 0.151 to 0.644, whereas the expected heterozygosity ranged from 0.213 to 0.847. The polymorphism data content of most sites was > 0.5, which indicated that the designed sites had high polymorphism. Structural analysis results indicated that GM, HD, and NYYZ had similar genetic structures across the five populations. The Nei’s genetic distance (Ds) between HD and NYYZ populations was the smallest (Ds=0.0624), whereas that between HD and QDY populations was the largest (Ds=0.2364). The UPGMA tree showed that HD were initially grouped with NYYZ, followed by GM, and then with QDDY. Furthermore, cross-species amplification tests were conducted for Metaphire guillelmi, which indicated that the presented markers were usable for this species. This study comprised a preliminary study on the genetic diversity of M. vulgaris, which provides basic data for future investigations into this species.